2011
DOI: 10.2190/pm.41.3.f
|View full text |Cite
|
Sign up to set email alerts
|

Active Depression is Associated with Regional Adiposity in the Upper Abdomen and the Neck

Abstract: The results of this study confirm the hypothesis of a high stress level with a disturbed hypothalamic-pituitary-adrenal (HPA) axis leading to a Cushing-like habitus and high visceral fat levels. The increased fat levels at the arms, as well as the whole body fat may be well-founded by a lack of activity in depression. These effects should be evaluated in further longitudinal studies investigating patients with a depressive syndrome and after remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Inability to distinguish subcutaneous and visceral adipose tissue (SAT and VAT, respectively) using measures such as body mass index (BMI) and waist circumference may explain some of the discrepancies. Previous studies have shown a significant positive association between depressive symptoms and VAT, but not SAT, particularly among women (Thakore et al, 1997; Everson-Rose et al, 2009; Ludescher et al, 2011; Murabito et al, 2013). Few studies have reported on the association between depressive symptoms and intra-abdominal fat (Kahl et al, 2005; Lee et al, 2005; Weber-Hamann et al, 2006; Vogelzangs et al, 2008; Everson-Rose et al, 2009; Greggersen et al, 2011; Murabito et al, 2013), although a positive bidirectional relationship has been suggested among an elderly population (Vogelzangs et al, 2008, 2010).…”
Section: Introductionmentioning
confidence: 80%
“…Inability to distinguish subcutaneous and visceral adipose tissue (SAT and VAT, respectively) using measures such as body mass index (BMI) and waist circumference may explain some of the discrepancies. Previous studies have shown a significant positive association between depressive symptoms and VAT, but not SAT, particularly among women (Thakore et al, 1997; Everson-Rose et al, 2009; Ludescher et al, 2011; Murabito et al, 2013). Few studies have reported on the association between depressive symptoms and intra-abdominal fat (Kahl et al, 2005; Lee et al, 2005; Weber-Hamann et al, 2006; Vogelzangs et al, 2008; Everson-Rose et al, 2009; Greggersen et al, 2011; Murabito et al, 2013), although a positive bidirectional relationship has been suggested among an elderly population (Vogelzangs et al, 2008, 2010).…”
Section: Introductionmentioning
confidence: 80%
“…Recently, a few studies have demonstrated that depressive symptoms may be an important predictor of abdominal obesity [10,16]. The most acceptable hypothesis for this relationship involves the hypothalamus-pituitary-adrenal (HPA) axis.…”
Section: Discussionmentioning
confidence: 99%
“…In most reports, central adiposity, whether directly quantified as visceral adipose tissue (VAT), 1, 3, 69, 11, 15, 16 or indirectly estimated as a waist-to-hip ratio, 4, 5, 8, 10, 17, 18 accounted for much or all of the relationship between excessive weight and depressive morbidity. Some reports also found that the relationship between VAT and depressive illness was restricted to, or more robust in, overweight/obese individuals.…”
Section: Introductionmentioning
confidence: 99%